PM.50 Maternity Services in the Irish Mass Media: An Analysis of Media Content from 2007–2012. (26th April 2013) - Marron, A; Burke, G; Devereux, E; Breen, M
Abstract : The mass media play a key role in informing the public about matters of public interest and, critically, in the actual shaping of public opinion about those matters. With this in mind, the purpose of this study was to examine Irish media content and the manner in which it portrays the maternity services in Ireland. A quantitative content analysis was conducted over the five-year time period from 2007 to 2012. Using the Nexis-Lexis newspaper database, data were sampled from three broadsheet newspapers (the Irish Times, the Irish Independent and the Irish Examiner), one tabloid newspaper (the Irish Daily Mail) and the RTE website. Articles were measured according to a pre-defined coding scheme that included variables such as article placement, storey length, topic, etc. and they were then compared against existing medical statistics. The results showed that less than 1% of articles relating to the Irish maternity services received front page treatment over the five-year period. Medico-legal processes (18.8%), budgetary and staffing issues (15.8%) and specific high-profile cases of misdiagnosis or inappropriate treatment (9.7%) have predominated as the focus of coverage. The more clinical matters, such as breastfeeding (4.5%), neonatal care (3.3%) and post-natal depression (1.2%), have received relatively little examination. The need for the public to have access to accurate information about medical matters is clearly of fundamental importance. However, the findings of this research suggest that there is a discrepancy between media representations of these critical issues and the medical realities, which has the potential to undermine public perception.